An Assessment of the Selenium Status of Iodine-Deficient and Non-Iodine Deficient Filipino Children - Ma. Sofia Amarra (Science Diliman, 2002)
The aim of this study is to examine and compare blood selenium levels in iodine-deficient and non-iodine deficient children. Two groups of children were examined: one group with iodine deficiency (n=31) and the other group with normal iodine status (n=32). Blood was extracted by venipuncture from children aged 6-10 years attending first grade in Commonwealth Elementary School in Quezon City. Whole blood selenium was examined by electrothermal atomic absorption spectrophotometry (AAS). Iodine status was determined by goiter palpation and urinary iodine excretion. Mean selenium levels of deficient and non-deficient children were compared using T-test. Using a cut-off value of 60 mg Se/L whole blood, the proportion of children with normal and deficient iodine status who fell below this cut-off was compared using chi-square test. Whole blood selenium values ranged from 17.6 to 133.6 mg/L. There were no significant differences in mean selenium levels between children with normal and deficient iodine status. Children with normal iodine status had a mean blood selenium level of 55.87 ± 26.3 mg/L while children with deficient iodine status had a mean level of 58.76 ± 26.4 mg/L. Sixty percent of children had blood selenium levels below the arbitrary cut-off of 60 mg/L with no significant difference between groups (p = 0.165), indicating that selenium deficiency is prevalent in this group of children regardless of iodine status. Since selenium deficiency limits the response to iodine supplementation, further investigation is needed to determine whether the same situation exists in children from other areas.